DAMPAK PEMEKARAN DESA TERHADAP INFRASTRUKTUR DESA PAKUURE DUA KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Grace A. A. G. Panambunan; Paulus A. Pangemanan; Benny A. B. Sagay (Sam Ratulangi University, 2018)
This study aims to determine the impact of the expansion of Pakuure Dua village on village infrastructure. The study was conducted from October to December 2017 Determination of the number of samples taken purposively (Purposive Sampling) The research method using descriptive analysis with informants of the local community along with village tools that will be presented in tabular form. The resulting data was analyzed using Likert scale. The result of the research concludes that the expansion of Pakuure Dua village has a positive impact on the acceleration of infrastructure development. This can be proved by the repair of roads in each aisle that used to be potholes built into asphalt road, concrete rebound road, hotmix asphalt road. The construction of the bridge between the hallway to the school and the field, the construction of the school building felt by the community is very good. With equitable road construction, ease of communication between community and government is also equitable, smooth communication and transportation activities also make a very good economic gain for the people of Pakuure Dua village.